The Relationship between Intellectual Capital and Competitive Advantages in Financial Public Sector with Application at Banque Misr in Egypt - Hussein, Marwa (The Arab Journal of Administration, 2022)
The main purposes of this research are to explore the intellectual capital, clarifying the dimensions of intellectual capital, in addition to investigate the relation between the components of intellectual capital and competitive advantage in the financial public sector. The research population focuses on the Egyptian public banks. Literature review, journals and books are used in describing the theoretical framework such as components of intellectual capital and the competitive advantages that also help in analyzing the relationship between the intellectual capital and competitive advantages. Previous studies rarely examined the connection and relevancy of intellectual capital, and the competitive advantage in the financial public sector especially in the public banks. The research concluded a set of results; the most important is that there is a significant positive relationship between the intellectual capital and competitive advantage in public banks. Finally, the research recommended a set of recommendations that would support decision makers to promote competitive advantage.